Pediatric Airway Assessment Tool (PAAT): A Rating Tool to Assess Resident Proficiency in Simulated Pediatric Airway Skills Performance - Wing, Robyn (MedEdPORTAL, 2020)
INTRODUCTION: The Accreditation Council for Graduate Medical Education has identified the need for assessment of core skills for pediatric and emergency medicine residents, which includes pediatric airway management. Although there are standard courses for pediatric airway management, there is no validated tool to assess basic and advanced pediatric airway skills performance. Our objective was to develop a simulation-based tool for the formative assessment of resident pediatric airway skills performance that was concise, yet comprehensive, and to evaluate the evidence supporting the argument for the tool's validity. METHODS: We developed a pediatric airway assessment tool (PAAT) to assess six major domains of pediatric airway skills performance: basic airway maneuvers, airway adjuncts, bag-valve mask ventilation, advanced airway equipment preparation, direct laryngoscopy, and video laryngoscopy. This tool consisted of a 72-item pediatric airway skills assessment checklist to be used in simulation. We enrolled 12 subjects at four different training levels to participate. Assessment scores were rated by two independent expert raters. RESULTS: The interrater agreement was high, ranging from 0.92 (adult bagging rate) to 1 (basic airway maneuvers). There was a significant trend of increasing scores with increased training level. DISCUSSION: The PAAT demonstrated excellent interrater reliability and provided evidence of the construct's validity. Although further validation of this assessment tool is needed, these results suggest that the PAAT may eventually be useful for assessment of resident proficiency in pediatric airway skills performance.